Use of gamification to increasing motivation in learning - Ayesha Zafar; Bagia Maulana Patah; Syelma Nuraida Fatya (Curricula: Journal of Curriculum Development, 2022)
The industrial revolution 4.0 became a driver of progress for all fields of life. In the field of education, era 4.0 made the old way of learning must be improved along with technological developments. One of them is gamification, a learning approach that uses several elements in games that aim to motivate students in the learning process so that they feel comfortable and have fun. This study uses a survey method, with the aim of knowing the responses, motivations, and interests of respondents related to this gamification. The survey was conducted using a google form, and distributed online to respondents through various communication media. The data is generated from research in the form of a bar chart. Then, this data is processed and the difference value is obtained from each question. Description of the research developed based on the questions in the questionnaire. The results of the study show that students like the learning process by gamification because students with a ranking game system have an award. Results Based on the research, students like learning by gamification. It should be explained that gamification is not just making a game. However, using the game system in real life. So, it is necessary to conduct further research on ways to develop gamification to increase students learning motivation.   Abstrak Revolusi industri 4.0 menjadi pendorong kemajuan salah satunya dalam bidang pendidikan yang membuat cara belajar harus ditingkatkan seiring dengan perkembangan teknologi. Metode gamifikasi sebagai pendekatan pembelajaran menggunakan beberapa elemen dalam gim bertujuan untuk memotivasi peserta didik dalam proses pembelajaran. Gamifikasi menjadi salah satu metode yang banyak digunakan karena dianggap dapat meningkatkan motivasi dan memberikan daya tarik kepada peserta didik dalam melaksanakan proses pembelajaran. Penelitian ini menggunakan metode survey. Hasil penelitian menunjukkan peserta didik termotivasi apabila proses pembelajaran dilakukan dengan cara gamifikasi karena peserta didik menyukai sistem gim dengan pemeringkatan yang memiliki sebuah reward. Perlu dipahami bahwa gamifikasi tidak hanya tentang sebuah gim namun, menggunakan sistem gim dalam kehidupan nyata. Perlu diadakan penelitian lebih lanjut mengenai cara-cara mengembangkan gamifikasi untuk meningkatkan motivasi belajar peserta didik agar metode gamifikasi ini dapat semakin beragam. Kata Kunci: Gamifikasi; inovasi pembelajaran; motivasi belajar